Heat tolerance decreases and cold tolerance increases with elevation for a species-rich insect family on a tropical volcano - Alexandre M. M. C. Loureiro; Winnie Hallwachs; Daniel H. Janzen; M. Alex Smith (Proceedings of the National Academy of Sciences, 2026)
The climate crisis is moving the high ambient temperatures common in lower elevation tropical forests upslope into areas where they would not have occurred historically. Tropical invertebrates may be particularly vulnerable to such changes. Here, our goal was to understand whether the distribution of heat and cold tolerances along an elevational gradient in northwestern Costa Rica predicted by theory were present for a leaf-litter inhabiting insect community of rove beetles (Staphylinidae: Coleoptera). We found that heat tolerance decreased, and cold tolerance increased with elevation, supporting the predictions. High elevation communities may not be capable of tolerating the rising temperatures that come with climate change, while low elevation communities are already experiencing environmental temperatures that may meet or exceed their thermal limits. While the forests in the low elevation more frequently exhibit temperatures that meet or exceed the heat tolerances for the beetle community, the soil will offer a buffered refuge for some time. The decline in thermal tolerance that we show here is predicted by theory yet is inconsistent with the values for insect species in the thermal tolerance literature. This reinforces the need for a better understanding of the thermal tolerances of diverse assemblages of tropical species that are likely to experience complicated and negative impacts of climate change.